Article Reviews: Bioethanol Production from Biomass Waste Using Fermentation with The Assistance of Yeast - Wiwik Pratiwi; Ni Made Suaniti (University of Jember, 2023)
Bioethanol is a biomass-based ethanol compound containing starch, sugar, and cellulose. The most common production of bioethanol uses hydrolysis and fermentation methods. The following article aims to compare the levels of bioethanol produced from various types of biomass using multiple methods. The process can vary in the concentration of acids and bases used in hydrolysis, fermentation time, and yeast mass. The article review results found that the highest bioethanol content was obtained from bioethanol made from bagasse, with an ethanol content of 41% by adding 1% sodium hydroxide to dextrose agar (PDA) media.